2020
DOI: 10.1088/1757-899x/862/6/062099
|View full text |Cite
|
Sign up to set email alerts
|

Heat and mass transfer in unit of cooling tower filler with advanced gas-liquid contact surface

Abstract: On a global scale, many cooling towers and contact elements occur in a variety of types. In this paper, a new design of the tower with the technology of contactless evaporation cooling has been presented. Experimental studies of the efficiency of heat and mass transfer processes in the inclined-corrugated element with the advanced gas-liquid contact surface as metal mesh were performed. Results of the change in the efficiency of heat and mass transfer processes from various gas velocity and the ratio of mass f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…More detailed descriptions of the experimental setup with the main design features are given in papers [11][12][13]. Various instruments were used to measure and control the parameters during the experiments, designated in the diagram (figure 1) as "T, F, φ," the characteristics given in table 1.…”
Section: Methodsmentioning
confidence: 99%
“…More detailed descriptions of the experimental setup with the main design features are given in papers [11][12][13]. Various instruments were used to measure and control the parameters during the experiments, designated in the diagram (figure 1) as "T, F, φ," the characteristics given in table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Even though the cooling tower fill structure can be quite similar to an internal flow with baffles and ribs, the literature is almost non-existent, particularly in the scope of internal flow with obstacles or even in the cooling tower studies. There are various film-type cooling tower fill designs available, consisting of different geometries of obstacles such as corrugated, 3 wave surface, straight, and zig-zag type fill. 4 Each has a varying effect on fluid film rate and airflow.…”
Section: Introductionmentioning
confidence: 99%
“…So far, a novel fill pack has been developed, consisting of inclined-corrugated contact elements [26]. A previous study of the dynamics of liquid and gas flows [27,28] showed the possibility of uniform distribution of liquid along the cooling tower's cross-sectional area.…”
Section: Introductionmentioning
confidence: 99%